Tuvan music and its discography (principal names, titles, issues of description) - Abildsnes, Morten (The New Research of Tuva, 2017)
The article presents the author’s work on systematizing the discography of 20th century Tuvan music. The author has been collecting the material for many years and is planning to publish the separate edition of “Tuvan music on compact disks”. The aim of the project is to let all the interested parties, including the Tuvans, to learn about the distribution of Tuvan music around the world. Western CDs are comparatively rarely sold in Tuva. Recording and releasing such disks is usually associated with the tours of Tuvan musicians abroad.The discography starts with the records of Tuvan music on seven disks released by the Moscow Factory of Sound Recording in 1934. The second series of Tuvan music records, which appeared on 17 disks in 1958 is little known. In 1971 the first long-play disk with Tuvan tunes “Tyva aialgalar / Melodii Tuvy” was released. “Sayany” and “Ayan” ensembles recorded mini-albums in 1980’s. The last vinyl mini-albums of Tuvan music are probably the annexes to academic editions of Tuvan folklore.The full discography of CDs includes disks released outside of Tuva – in Western Europe, USA and Moscow. First CDs were released in 1989: a collection of concert records of Soviet artists and the collection of music related to the documentary about Tuva “The Herders of Mongun-Taiga” (Great Britain). The biggest discography of all the Tuvan artists belongs to Sainkho Namtchylak. Her disks are well represented in free international database Discogs, while information about other Tuvan artists is less complete. The article also presents samples of Tuvan throat-singing in the works of other musical collectives and names their disks.Among solo and joint projects in the discography, “Huun Huur Tu” and “Yat Kha” are represented widely. Commercial interest in Tuvan music peaked  in 1999, when one of the biggest labels “Warner Bros” released a solo CD of Kongar-ol Ondar. Since then number of Tuvan CDs has been decreasing.Lately, we have seen albums of digital files available for downloading or streaming. In Tuva tape cassettes have been the most popular medium for music distribution. CDs are taking first place now, but mainly CD-Rs.
Keywords: Tuva; Tuvan music; discography; disk; vinyl disk; throat singing; xöömei; CD; Tuvan musicians; musical band; “Melodia”; “Huun Huur Tu; “Yat Kha”; Sainkho Namtchylak; Kongar-ool Ondar